2009
DOI: 10.1021/om900354v
|View full text |Cite
|
Sign up to set email alerts
|

Carbene Complexes Made Easily: Decomposition of Reissert Compounds and Further Synthetic Approaches

Abstract: New methods for the preparation of NHC-metal complexes have been developed. It was shown that a nitrile group in Reissert analogous compounds can act as a good leaving group in thermal elimination, resulting in carbene formation. Moreover potassium carbonate was introduced as a highly efficient and mild reagent for the generation of N-heterocyclic carbene complexes in good to excellent yields, even in water, as the most environmentally friendly medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…The characteristic downfield signals for the NC H N + protons of the imidazol(in)ium salts disappeared in the 1 H NMR spectra of complexes 4a , 4b , 5a , 5b , 6a , 6b . These complexes exhibit 13 C chemical shifts and coupling constants that are comparable to those of other reported NHC–rhodium(I) complexes . 13 C chemical shifts showed that C carbene is substantially deshielded.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The characteristic downfield signals for the NC H N + protons of the imidazol(in)ium salts disappeared in the 1 H NMR spectra of complexes 4a , 4b , 5a , 5b , 6a , 6b . These complexes exhibit 13 C chemical shifts and coupling constants that are comparable to those of other reported NHC–rhodium(I) complexes . 13 C chemical shifts showed that C carbene is substantially deshielded.…”
Section: Resultssupporting
confidence: 79%
“…Practically almost all catalytic studies have been devoted to saturated imidazolin‐2‐ylidene and unsaturated imidazol‐2‐ylidene bearing symmetric aryl or benzyl substituents, while related dissymmetrically substituted imidazol(in)‐2‐ylidenes have not received sufficient attention . Therefore, a comparative experimental study of NHCs with Mes and CH 2 Mes substituents on the N atoms is presented.…”
Section: Introductionmentioning
confidence: 99%
“…38 4,5-dimethyl-1,3-diisopropyl-imidazol-2-ylidene copper chloride was prepared by following established literature methods for NHC CuCl. 39 4,5-dimethyl-1,3-diisopropyl-imidazol-2-ylidene 40 and 1,3-diisopropyl-imidazolinium chloride 41 were prepared according to literature. The diethyl ether adduct of lithium hexamethyldisilazide was prepared according to literature.…”
Section: Resultsmentioning
confidence: 99%
“…We developed a synthetic method for obtaining these known compounds [44,46,48,49,[52][53][54][55][56], which does not require the use of the isolated free carbenes or the use of the corresponding Ag(I)-NHC transmetallating agents. In general, the synthesis of 1-4 (Scheme 1) involved stirring of the respective 1,3diarylimidazolium or 1,3-diarylimidazolinium salt in toluene at 70 °C together with [RhCl(cod)]2 and K2CO3 as an efficient and mild base (A) [47] or with [Rh(OH)(cod)]2 (no base added; B). After removal of the toluene solvent the products were dissolved in CH2Cl2-ethyl acetate and purified by passing through a short silica column; complexes 1-4 were isolated in 58-88% yield.…”
Section: Synthesis and Characterization Of The [Rhcl(cod)(nhc)] Complmentioning
confidence: 99%